Conventional and bubbled slab strips under limited repeated loads: A comparative experimental study - Hussain A. Jabir; Jasim M. Mhalhal; Thaar S. Al-Gasham (Case Studies in Construction Materials, 2021)
This work primarily aimed to compare the bubble slabs experimentally with solid slabs under the influence of limited repeated four-point loads. Therefore six slab strips were manufactured in the same forms, except the cross-section type. Three were solid, and the others were voided due to placing 70 mm-diameter balls inside them. In addition, the shear span to effective depth ratio (a/d) was also studied. Accordingly, one slab from each type was tested, with the a/d being either 2, 3.5, or 5. The applied loads were repeated ten cycles at a load level of 25 kN, representing 70 % of the ultimate load estimated according to the ACI-19 code, and then lasted gradually until the slabs' collapse. The results recorded that the balls' presence made slabs failed abruptly due to shear mode regardless of the a/d. For the same slab type, the slabs' strength, stiffness, and toughness reduced as the a/d was increased; nevertheless, the ductility showed an opposite trend. Compared to solid similars, the bubble slabs' mechanical measurements, excluding the service stiffness, dropped notably. However, the stiffness decay was small, below 15 %. Moreover, sustainability analysis was performed, and the voided slabs were found to be more eco-friendly than solid ones due to reductions in the CO2 emission and consumed embodied energy, about 14 % and 10 % below those of the solid slabs.